Noninvasive approach to mend the broken heart: Is "remote conditioning" a promising strategy for application in humans - Ravingerová, Táňa; Farkašová, Veronika; Griecsová, Lucia; Muráriková, Martina; Carnická, Slavka; Lonek, L'ubomír; Ferko, Miroslav; Slezak, Jan; Zálešák, Marek; Adameova, Adriana; Khandelwal, Vinoth K M; Lazou, Antigone; et al. (Canadian journal of physiology and pharmacology, 2017)
Currently, there are no satisfactory interventions to protect the heart against the detrimental effects of ischemia-reperfusion injury. Although ischemic preconditioning (PC) is the most powerful form of intrinsic cardioprotection, its application in humans is limited to planned interventions, due to its short duration and technical requirements. However, many organs/tissues are capable of producing "remote" PC (RPC) when subjected to brief bouts of ischemia-reperfusion. RPC was first described in the heart where brief ischemia in one territory led to protection in other area. Later on, RPC started to be used in patients with acute myocardial infarction, albeit with ambiguous results. It is hypothesized that the connection between the signal triggered in remote organ and protection induced in the heart can be mediated by humoral and neural pathways, as well as via systemic response to short sublethal ischemia. However, although RPC has a potentially important clinical role, our understanding of the mechanistic pathways linking the local stimulus to the remote organ remains incomplete. Nevertheless, RPC appears as a cost-effective and easily performed intervention. Elucidation of protective mechanisms activated in the remote organ may have therapeutic and diagnostic implications in the management of myocardial ischemia and lead to development of pharmacological RPC mimetics.
Keywords: Animals; ischemické přivykání; Regional Blood Flow; Myocardial Reperfusion Injury; výsledek terapie; Time Factors; časové faktory; lidé; signální transdukce; Treatment Outcome; reperfuzní poškození myokardu; Signal Transduction; modely nemocí na zvířatech; Ischemic Preconditioning, Myocardial; Disease Models, Animal; regionální krevní průtok; Myocardial Infarction; zvířata; Myocardium; myokard; infarkt myokardu; Humans